Circulating progenitor cells in rheumatoid arthritis: association with inflammation and oxidative stress. (May 2014) - Lo Gullo, A; Mandraffino, G; Sardo, MA; D'Ascola, A; Mamone, F; Loddo, S; Alibrandi, A; Imbalzano, E; Mandraffino, R; Mormina, E; Saitta, C; Lo Gullo, R; et al.
<x xml:space="preserve">Abstract</x> Objectives: To evaluate the association between inflammation, oxidative stress, and circulating progenitor cell (CPC) number and redox equilibrium, vascular lesions and accelerated atherosclerosis in rheumatoid arthritis (RA). Method: Circulating CD34+ cells were isolated from 33 RA patients and 33 controls. Reactive oxygen species (ROS) levels and mRNA expression of manganese superoxide dismutase (MnSOD), catalase (CAT), glutathione peroxidase type 1 (GPx-1) antioxidant enzymes, and the gp91phox-containing nicotinamide adenine dinucleotide phosphate (NADPH) oxidase NOX2 were measured in CD34+ cells. C-reactive protein (CRP), fibrinogen, erythrocyte sedimentation rate (ESR), carotid intima–media thickness (cIMT), and arterial stiffness (AS) were also evaluated. We investigated the relationships between inflammatory markers, vascular parameters, cell number, and antioxidant enzymes. Results: CD34+ cell number was lower in RA patients than in controls. In CD34+ cells from RA patients, ROS levels, MnSOD mRNA, and NOX2 mRNA were higher, while mRNA expression of GPx-1 and CAT was significantly lower. The AS, pulse wave velocity (PWV), and augmentation index (AIx) were higher, as was cIMT. CD34+ cell number was inversely correlated with CRP, ROS, PWV, and AIx, and with the CAT/MnSOD and GPx-1/MnSOD ratios. CRP was correlated with MnSOD mRNA, PWV, and AIx but not with CAT and GPx-1 mRNA. Conclusions: Our data show a link between inflammation, oxidative stress, and the impairment of the antioxidant system of CPCs and their number, and with arterial stiffness in RA subjects. This could suggest a perspective on the accelerated development of vascular damage and atherosclerosis in RA.